2022
DOI: 10.1177/00332941221087915
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Based Parenting and Academic Motivation in Adolescents Returning to School After COVID-19 School Closure: Exploring the Effect of School Belonging and Strength Use

Abstract: The present study aimed to examine whether the level of strength-based parenting a student receives during remote learning affects their levels of academic motivation once returning to school. Additionally, the study sought to explore whether school belonging mediated the association between strength-based parenting and academic motivation and whether student strength use moderated this mediating relationship. The sample comprised of secondary school students who had recently returned back to campus, following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…It has long been demonstrated that children and youth who report meaningful connections with their parents, teachers, and school environments have lower levels of mental health difficulties [63,64]. The included studies highlighted that connectedness during the COVID-19 pandemic had a significantly positive impact on child and youth health [24,[65][66][67], and personal relations among children and youth with their educational teachers, parents, and peers was a hallmark of most included studies. Accordingly, dedicated time for social activity in educational settings that includes opportunities to connect with teachers and peers was one approach that was frequently referred to as necessary to continue post-COVID-19, which may occur through facilitating open discussions [66,68], conducting team-based activities [66], or enhancing peer learning activities [69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been demonstrated that children and youth who report meaningful connections with their parents, teachers, and school environments have lower levels of mental health difficulties [63,64]. The included studies highlighted that connectedness during the COVID-19 pandemic had a significantly positive impact on child and youth health [24,[65][66][67], and personal relations among children and youth with their educational teachers, parents, and peers was a hallmark of most included studies. Accordingly, dedicated time for social activity in educational settings that includes opportunities to connect with teachers and peers was one approach that was frequently referred to as necessary to continue post-COVID-19, which may occur through facilitating open discussions [66,68], conducting team-based activities [66], or enhancing peer learning activities [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, dedicated time for social activity in educational settings that includes opportunities to connect with teachers and peers was one approach that was frequently referred to as necessary to continue post-COVID-19, which may occur through facilitating open discussions [66,68], conducting team-based activities [66], or enhancing peer learning activities [69,70]. , demonstrated that enhanced positive teacher and student relationships mitigated the impacts of peer victimization and mental health difficulties for younger students during the pandemic; these relationships were also defined by parental mediation and approaches [24,71]. The pandemic revealed that students' social-emotional development is inadequately supported even in normal times, calling for an urgent need for more effective social-emotional learning opportunities and innovative approaches to expand student supports.…”
Section: Discussionmentioning
confidence: 99%
“…It is a positive parenting style that seeks to "deliberately identify and cultivate positive states, positive processes, and positive qualities in one's children" (Waters, 2015, p. 690). This parenting approach emphasizes on recognizing, promoting, and developing child's strengths and positive attributes to promote mental health and well-being (Allen et al, 2022;Arslan et al, 2022a). Parents respect their children's interests, encourage them to explore, and help them build self-confidence and a positive sense of self (Arslan et al, 2022b;Jach et al, 2018).…”
mentioning
confidence: 99%
“…The COVID-19 pandemic caused negative effects on the physical (Liu et al, 2020), and psychosocial health and well-being of children and adolescents (Arslan et al, 2022;Avcı, 2023;Gifford-Smith & Brownell, 2003;Majercakova Albertova & Bolekova, 2022;Panda et al, 2021;Ravens-Sieberer et al, 2021;Xie et al, 2020;Zhou et al, 2020b). Many international studies confirm the burden of children and adolescents, throughout the COVID-19 pandemic, with anxiety, depression and post-traumatic stress (Kar & Bastia 2006;Ma et al, 2021;Stavridou et al, 2020;Yıldırım & Çiçek, 2022).…”
mentioning
confidence: 99%